Proposal of instrument for collection of data of nursing in a Unit of Intensive Therapy based on horta - Luciano Ramos de Lima; Marina Morato Stival; Luciene Ramos de Lima; Cleydson Rodrigues de Oliveira; Tânia Couto Machado Chianca (Universidade Federal de Goias, 2006)
The nursing process is a method that makes it possible to the nurse to develop and apply the technical-scientific knowledge, to evidence his practical professional and to provide a systemized assistance. The purpose of this study is to elaborate and to validate an instrument of collection of data for interned patient in the intensive care unit (UTI). The study was divided in three-stages - construction of the instrument based on Wanda A. Horta's Theory of Basic Human Needs (BHN), validation of content and appearance and refinement of the instrument. The validation of appearance and content was carried through by 10 nurses specialist. The appraisers had suggested some modifications, in the content and also in the appearance, and had judged that the instrument will be able to facilitate the collection of data, the analysis, the judgment and a proposal of specific interventions of nursing to the raised problems.